Optimization of High Hydrostatic Pressure Treatments on Soybean Protein Isolate to Improve Its Functionality and Evaluation of Its Application in Yogurt - Chenxiao Wang; Hao Yin; Yanyun Zhao; Yan Zheng; Xuebing Xu; Jin Yue (Foods, 2021)
This work aimed to improve the functional properties of soybean protein isolate (SPI) by high hydrostatic pressure (HHP) and develop SPI incorporated yogurt. Response surface methodology (RSM) was used to optimize the HHP treatment parameters, including pressure, holding time, and the ratio of SPI/water. Water holding capacity, emulsifying activity index, solubility, and hardness of SPI gels were evaluated as response variables. The optimized HPP treatment conditions were 281 MPa of pressure, 18.92 min of holding time, and 1:8.33 of SPI/water ratio. Water and oil holding capacity, emulsifying activity, and stability of SPI at different pH were improved. Additionally, relative lipoxygenase (LOX) activity of HHP treated SPI (HHP-SPI) was decreased 67.55 ± 5.73%, but sulphydryl group content of HHP-SPI was increased 12.77%, respectively. When incorporating 8% of SPI and HHP-SPI into yogurt, the water holding capacity and rheological properties of yogurt were improved in comparison with yogurt made of milk powders. Moreover, HHP-SPI incorporated yogurt appeared better color and flavor.